Qualidade de vida relacionada à saúde bucal em pacientes diagnosticados com acromegalia - CAMPELO, Renata Carvalho (2020)
Acromegaly is a disease caused by the excessive production of growth hormone and insuline-like type I, caused in 95% of cases by a pituitary tumor. Chronic exposure to these substances leads to an increase in the occurrence of cardiac, respiratory, endocrine and joint complications, among others. Such hormonal changes also contribute to changes in the soft and hard tissues of the face, leading to facial asymmetry, jaw growth, mandibular protrusion, macroglossia, diastema, etc. Acromegaly and all its changes have a negative impact on oral health and the quality of life of affected individuals. Therefore, the aim of our study was to investigate the quality of life related to oral health and its association with the presence of malocclusion, socio-demographic factors and general health in patients with acromegaly. Thirty-four acromegalic patients were evaluated through interviews, to collect sociodemographic data and habits; clinical evaluation, to identify orofacial changes; and application of the OHIP-14 questionnaire to assess oral health-related quality of life. Statistical analysis included correlation measures, multiple linear regression and structural equation model (SEM), adopting a significance level of 5% (P <0.05). The sample consisted of 58.8% women and 41.2% men, with an average age of 50.7 ± 15.7 years. The average of the total OHIP-14 score was 15.7 ± 7.7 and 79.4% had the prevalence of at least one affected factor. SEM standardized coefficients (CP) showed the presence of arthritis (CP = 0.467, P <0.05) and smoking history (CP = 0.459, P <0.05) were associated with the negative impact on related quality of life oral health. In addition, mandibular protrusion, anterior open bite, anterior crossbite and diastema are related to the worsening of different dimensions of OHIP-14. The findings of this study allow us to conclude that the habit of smoking, the occurrence of rheumatoid arthritis and orofacial changes (mandibular protrusion, open bite, cross bite and diastema) negatively impact the quality of life related to oral health in patients diagnosed with acromegaly. Therefore, the results presented highlight the importance of early diagnosis of this disease and the need to minimize and / or control these changes to ensure adequate quality of life and oral health for these patients.